Estimation of Serum Procalcitonin Levels in Patients with Sepsis - Goel, Aarzoo; Pandey, Amarnath; Pokhriyal, Parshant; Kumari, Muskan; Nautiyal, Anuj (Journal of Neonatal Surgery, 2025)
Introduction: Sepsis and SIRS share overlapping clinical features but differ fundamentally in their underlying pathophysiology. Both represent systematic inflammatory states; yet, the source and progression of immune activation diverge significantly between infectious and non-infectious etiologies. These differences become critical when attempting early diagnosis, where clinical science alone is insufficient, and biochemical markers, such as PCT, gain diagnostic relevance. Aim: To determine the Day 1 serum Procalcitonin level in patients with sepsis and to assess the Day 1 serum procalcitonin concentration with duration of stay. Materials and Methods: This research was designed as a prospective cohort study, which was conducted in the department of internal medicine at SGRRIM&HS and SMIH Dehradun on 150 patients of both genders above age 18 years with clinical evidence of heart failure who presented within 24-36 hours of illness with suspected sepsis and were admitted to the ICU. The study duration was 18 months. Serum procalcitonin was measured using a standard immunoassay method. Haematological tests, biochemical tests, and infectious disease tests were performed to confirm the specific infection. Chi-square tests and t-tests were performed for comparative analysis. Results: A total of 150 patients [mean age was 34.2±8.1 years (18-40 years), mean age of 52.4±6.3 years (41-60 years), and mean age of 68.7±5.9 years (above 60)] were included in the study. Higher PCT levels were associated with an increased mortality rate. The most significant mortality was observed in patients with PCT levels greater than 30 ng/mL, with 68% of the patients expiring, showing a strong and statistically significant association (p value = 0.001). A higher level of PCT was observed in patients with septic shock, suggesting that elevated PCT levels may be an indicator of septic shock in patients. 83.3% of patients had septic shock and expired, which indicates that septic shock is strongly associated with mortality (p-value = 0.03). PCT level also influences the ICU stay duration. Conclusion: The study indicates that PCT serves as a diagnostic and monitoring tool, enabling clinicians to enhance patient care, reduce mortality associated with sepsis, and improve patient outcomes across various healthcare settings.